HUBUNGAN BAHAN AJAR EBOOK BERBASIS ANDROID DAN BERPIKIR KRITIS KONSEP SISTEM PERNAPASAN MANUSIA TERHADAP HASIL BELAJAR SISWA KELAS VIII SMP NEGERI 3 BULA - Siti Mia Soulissa; Alwi Smith; M Nur Matdoan (Program Studi Pendidikan Biologi FKIP Unpatti, 2020)
Background: This study aims to determine the relationship of e-book based teaching materials on Android and think critically to the learning outcomes of the concept of the human respiratory system. Method: The type of research used is quase experimental research with one group pre-test post-test research design. This research was carried out at SMP Negeri 3 Bula on October 29, 2018 - November 29, 2018. The sample in this study was eighth grade students consisting of 22 people, data collection instruments in the form of learning outcomes tests and questionnaire sheets. Data were analyzed using correlation test with the help of SPSS Version 23.0 for windows. Results: There is a very weak relationship of teaching materials based on android e-books on the learning outcomes of the concept of the human respiratory system with a correlation value -, 145. There is a very weak relationship with learning outcomes with a correlation value (r) of - 104. There is a very strong and significant relationship between teaching materials based on android e-books and critical thinking together on the learning outcomes of the concept of the human respiratory system with a correlation value (r) of 0.971. Conclusion: Both variables have a very weak negative relationship. Critical thinking on learning outcomes has a very weak negative relationship. Critical thinking contributes to learning outcomes of 10.4% and the remaining 89.6% comes from other factors. There is a relationship between Androidbased Ebook teaching materials and critical thinking on learning outcomes